A Mechanistic In Vivo/Ex Vivo Pharmacokinetic‐Pharmacodynamic Model of Tenofovir for HIV Prevention. (6th February 2021) - Jayachandran, Priya; Garcia-Cremades, Maria; Vučićević, Katarina; Bumpus, Namandjé N.; Anton, Peter; Hendrix, Craig; Savić, Radojka
Abstract : Defining tissue and plasma‐specific prophylactic drug concentrations is central to pre‐exposure prophylaxis product development for sexual transmission of HIV‐1. Pharmacokinetic (PK) data from study RMP‐02/MTN‐006 comparing single dose oral tenofovir disoproxil fumarate with single and multiple dose rectal tenofovir (TFV) gel administration in HIV‐1 seronegative adults was used to construct a multicompartment plasma‐rectal tissue population PK model for TFV and tenofovir‐diphosphate (TFVdp) in plasma and rectal tissue. PK data were collected in five matrices: TFV (plasma, rectal tissue homogenate), TFVdp (peripheral blood mononuclear cells, rectal mononuclear cells (MMCs), rectal tissue homogenate). A viral growth compartment and a delayed effect compartment for p24 antigen expression measured from an ex vivo explant assay described HIV‐1 infection and replication. Using a linear PK/pharmacodynamic model, MMC TFVdp levels over 9, 000 fmol/million cells in the explant assay provided apparent viral replication suppression down to 1%. Parameters were estimated using NONMEM version 7.4.